Maize response to sole and combined effects of nitrogen and nematode stresses (2021)
Crops grown on the field or in phytotrons are faced with different biotic stresses including plant-parasitic nematodes (PPNs) and abiotic stresses such as drought and poor soil fertility (low nitrogen levels). In this study, the interactive responses of a low-nitrogen tolerant variety LNTP-YC, and a regular variety BR-9928-DMRSR to Pratylenchus geae under four nitrogen-levels: no amendment; [TO], low nitrogen [100kg/ha NPK; T1], optimum nitrogen [200kgN/ha NPK + Urea; T2] and compost [10t/ha; T3] were investigated. The treatments were arranged in a 2 x 4 factorial fitted into randomised complete block design (RCBD) with four replicates. Data were collected on growth parameters (plant height and stem girth), yield components (number and weight of cobs), lesion score (LS), final nematode population (FNP) and reproductive factor (RF). Low nutrient stress in combination with nematode infection generally reduced maize growth and yield. Growth parameters of BR-9928-DMRSR variety were generally high while yield parameters of LNTP-YC variety were significantly greater than in BR-9928-DMRSR variety. However, T2 and T3 improved growth and yield of both maize varieties compared to TO, with T2 being superior to T3. Meanwhile, T3 reduced FNP more than T2. FNP (107.65) and RF (1.3) of P. geae on LNTP-YC variety and with T3 was significantly low compared to T2 (178, 3.34), TO (188, 3.6) and T1 (217, 5.0). In all the parameters considered, LNTP-YC outperformed BR-9928-DMRSR variety. In conclusion, soil amendment with optimum rate of nitrogen and compost reduced nematode population and enhanced maize growth, while low nitrogen in combination with nematode stress reduced maize yield.